ONBOARD COMPUTATIONAL FACILITY IN TERMS OF KNOWLEDGEBASE MANAGEMENT SYSTEMS - Vasiliy M. Trembach (Статистика и экономика)
The article considers approaches and usability techniques of onboard computational facilities for different purposes based on the knowledgebase management systems. Mechanisms and methods of the solution of some tasks are described. The demo version of the knowledgebase management system is shown.